Learning Time Management of Full Day School Students in Junior High School and Its Implication to Guidance and Counseling Services - Hasanah Hasanah; Daharnis Daharnis (Jurnal Neo Konseling, 2019)
Time management of learning is a way to manage time in using time effectively and efficiently by making plans, scheduling, prioritizing, managing control over time that can be seen from individual learning needs. The background of research is various problems that occur in the students time management of learning junior high school in schools that implement the full day school system. The problem at issue by junior high school students’ in schools that implement the full day school system is a matter of time and difficulty of responsibility in learning, organization, extracurricular activities and other additional activities. Counselors helps improve students’ skills and understanding of learning time management through guidance and counseling services. There are several guidance and counseling services that can be provided to student regarding learning time management issues supported by information services, content mastery services, group guidance services, individual counseling services and group counseling services. This study aims to describe the students’ time management of learning at junior high school 33 Padang, seen from the aspects of: (1) planning of goals and priorities, (2) planning and scheduling, and (3) implementation. This research uses quantitative descriptive methods. The study population was 371 at junior high school 33 Padang and a sample of 186 students were selected using the Simple Random Sampling technique. The instrument used was a study time management questionnaire. The students’ time management of learning in junior high school 33 Padang is relatively high, which is related to the students’ time management of learning in: (1) aspects of setting goals and priorities, (2) aspects of planning and scheduling, and (3) aspects of implementation is relatively high.